Comparisons of in situ Vp/Vs ratios and seismic characteristics between northern and southern California. Issue 3 (7th February 2022) - Lin, Guoqing; Peng, Zhigang; Neves, Miguel
SUMMARY: We present our estimations and comparisons of the in situ V p / V s ratios and seismicity characteristics for the Parkfield segment of the San Andreas fault in northern California and the San Jacinto Fault Zone and its adjacent regions in southern California. Our results show that the high-resolution in situ V p / V s ratios are much more complex than the tomographic V p / V s models. They show similar variation patterns to those in the tomographic V p models, indicating that V p / V s ratios are controlled by material properties but are also strongly influenced by fluid contents. In Parkfield, we observe velocity contrasts between the creeping and locked sections. In southern California, we see small-scale anomalous V p / V s variation patterns, especially where fault segments intersect, terminate and change orientations. In addition, our investigation confirms that the seismicity in Parkfield is more repeatable than in southern California. However, the earthquakes in the southernmost portion of the San Andreas fault, the trifurcation area of the San Jacinto Fault Zone and the Imperial fault are as much likely falling into clusters as those in Parkfield. The correlation of highly similar events with anomalous in situ V p / V s ratios supports the important role of fluids in the occurrence of repeating earthquakes. The high-resolution V p / V s ratio estimation method and the corresponding results are helpful for revealing roles of fluids in driving earthquake, fault interaction and stress distribution in fault zones.